Anti-predator behaviour of adult red-legged partridge (Alectoris rufa) tutors improves the defensive responses of farm-reared broods. Issue 3 (3rd May 2016) - Sánchez-García, C.; Alonso, M.E.; Tizado, E.J.; Pérez, J. A.; Armenteros, J. A.; Gaudioso, V. R.
Abstract: The aim of this work was to improve natural anti-predator behaviour of farm-reared gamebirds. We evaluated the anti-predator behaviour of reared red-legged partridge Alectoris rufa chicks kept in brooder houses in large groups (>350 chicks), trained and not trained by parent red-legged partridges acting as experienced tutors. The experiment consisted of two conditioned tests (a raptor model and a human) and two control tests, which were conducted during three consecutive phases of life (1–4, 15–17 and 30–32 d after hatching). The motor anti-predator behaviour, its duration, the intensity of response in chicks and alarm calls elicited by adults were recorded. Tutors elicited aerial alarm calls (76% of tests) and showed prolonged crouching (59% of tests) in response to the raptor model whereas uttering the ground alarm call (73% of tests) and showing vigilance behaviour (78% of tests) was the main pattern during the human test. Trained and not trained chicks showed similar motor behaviour in response to the raptor model (crouching) and the human test (escaping), but frequency of strong responses (all chicks responding) from chicks trained with tutors was double that of chicks trained without them, and chicks trained with tutors showed a higher frequency of long responses (41–60 s). This study indicates that anti-predator training programmes before release may improve behaviour of farm-reared partridges which may confer benefits to survival of birds.